Empowering Women Entrepreneurs in Brazil: An Analysis of 2010-2019 Trends - Souza Braz, Elisiane; Souza Almeida, Cleycianne; Gaspar Feitosa, Débora; Lima Campelo, Guaracyane; Hissa Teixeira, Keuler; Félix Gomes, José Weligton (Archives of Business Research, 2023)
This study undertakes a succinct literature review to delve into the importance of female entrepreneurship in Brazil, particularly focusing on the period from 2010 to 2019. By scrutinizing Brazilian Gross Domestic Product (GDP) data and referencing reports from the Global Entrepreneurship Monitor (GEM), the research effectively situates female entrepreneurship within the Brazilian economic context. Employing metrics such as Total Early-stage Entrepreneurial Activity (TEA) Rate, Established Business Ownership Rate (EBO), and Total Entrepreneurship Rate (TER), the study delves into the Total Early-stage Entrepreneurial Activity Rate across diverse demographics including age groups, income ranges, education levels, and sectors. Through correlation analysis and dispersion diagrams, intricate connections emerge between early-stage entrepreneurial rates and variables such as age, income, education, and sectors. This research unveils the profile and significance of Brazilian entrepreneurs, underscoring the pivotal role of women in nurturing economic and societal progress. Elevating women’s participation in entrepreneurship emerges as a cornerstone for transformative societal change, embodying ideals of self-sufficiency and empowerment. This research is classified within the realms of bibliographic, documentary, descriptive, and exploratory methodologies. Notably, the study reveals that female entrepreneurship significantly contributes to Brazil’s economic advancement, fostering both economic and social development.